ESTIMATION DE LA CONDUCTIVITE HYDRAULIQUE DE LA NAPPE DE TAFILALET PAR ANALYSE GEOSTATISTIQUE (SUD-EST DU MAROC) - Ilias Bouaamlat; Abdelkader Larabi; Mohamed Faouzi; Mahmoud Zemzami (European Scientific Journal, ESJ, 2015)
This article aims to present a methodology for geostatistical modeling which allows analysising the spatial variability and the estimating the values of hydraulic conductivity of the groundwater of Tafilalet. This study is performed with the GIS, based on the observed values of 78 boreholes drilled in the study area. Two types of experimental variograms were performed taking into account the appearance of isotropic and anisotropic and allowing to infer the spatial correlations existing between the values. These variograms have been modeled by two types of analytic functions; exponential and spherical. The performance of this model was evaluated by analyzing the errors of estimates calculated by the method of crossvalidation. The results correspond to thematic maps that are used for decision making and implementation of a hydrogeological model for the groundwater of Tafilalet.